Post-Doctoral and Non-Faculty Doctorate Researchers in Engineering Education: Demographics and Funding - Kehdinga George Fomunyam (African Journal of Inter-Multidisciplinary Studies, 2022)
The driving force behind research in many countries is funding for research and development. The research at postgraduate level is predicated on a core research group championed by one principal investigator which might include staff scientists, postdoctoral appointees, non-faculty doctorate researchers, or graduate students and they play major roles in supporting the day-to-day duties in a research laboratory in order to gain more knowledge to continue their own independent research careers. In this case study, postgraduate postdoctoral appointees and doctorate holding non-tenure researchers in engineering were the study group and secondary data from National Center for Science and Engineering Statistics (2018) was used in this study. From this result, it was noticeable that there were more of postdoctoral appointees in units much more than the other categories.  There were more males than females among postdoctoral appointees and non-faculty doctorate researchers in engineering education. Findings reveal that the most prominent primary sources of support for postdoctoral appointees are federal and nonfederal domestic. From the primary mechanism of support, research grants were the most available for post-doctoral appointees. This study therefore recommends that there should be more inclusion for females in engineering education and efforts be intensified on increasing funding in postdoctoral engineering education.